Analyzing the market and financial impacts of the State Bank of India’s Merger: A comprehensive Event Study - Sasikala, S.; Sudha, B.; N. Manju, Ms.; Ra. Yuvashree, M. (Edelweiss Applied Science and Technology, 2024)
This article presents detailed information about the event study that analyzed the market and financial impacts of the State Bank of India’s (SBI) merger. The merger of the SBI with its associate banks plays a significant role in the banking sector. The main aim of this study is to estimate the abnormal return and cumulative abnormal return test the significance of the shares of the SBI and also examine the impact of the merger of the SBI using Event study methodology. The market model is to be used in this study. The researcher has used the Wilcoxon Signed Ranked test for the event study to test the significance. The study reveals no significant difference in abnormal return of the SBI-merger during the pre and post-window periods. By applying the market model, a linear relationship between a stock return and market return be assumed. The findings of the study indicate that there is no significant relation between the pre and post-event windows in the abnormal returns. This suggests the market has already anticipated the effects of the merger. Moreover, the research will analyse the broader implications of the merger such as profitability, asset quality, and operational efficiency. The study contributes to the ongoing disclosure of the effectiveness of mergers in the banking sector and provides valuable insights for policymakers and investors.